The role of social media at Pegasus Steel South Africa, and the steel industry - Hardy, Christine (The IIE, 2020)
This research report is focused on the role of social media at Pegasus Steel, South Africa and the steel industry. The reasoning for this chosen topic is for the fact that there is a gap in the knowledge of what the role of social media is in the steel industry. It is important with the development in times that all businesses adapt to social media as a lot of companies are introducing it for the fact that it covers a wide range of audience for advertising purposes. The data collection method used was semi-structured interviews because it was best suited for qualitative data collection. The problem that the student encountered while doing the research was that the interviews were to take place during the Covid-19 outbreak. Thereafter, the student needed to change the way in which data was being collected. Therefore, the student’s approach was adapting to the change and using the online platform, Microsoft teams to do the interviews, as this is the channel that Pegasus Steel employees preferred most. The most significant findings were that the role of social media is of importance for predominately marketing and advertising.
Keywords: Social media; Steel industry; Advertising; COVID-19; South Africa